Growth of strategy sets, entropy and nonstationary bounded recall - Abraham Neyman; Daijiro Okada (Rutgers University, Department of Economics, 2005)
This paper initiates the study of long term interactions where players' bounded rationality varies over time. Time dependent bounded rationality is reflected in part in the number ψ(t) of distinct strategies in the first t-stages. We examine how the growth rate of ψ_i(t) affects equilibrium outcomes of repeated games, and, as a special case, we study the repeated games with nonstationary bounded recall.
Keywords: C72; C73; 330; Bounded Rationality; Strategy Set Growth; Strategic Complexity; Nonstationary Bounded Recall; Repeated Games; Entropy; Soziale Beziehungen; Beschränkte Rationalität; Zeit; Wiederholte Spiele; Entropie; Theorie